C Factor’s Conceptualization: Background And Perspectives - Agudelo Agudelo, Maria Fernanda; Patiño Velásquez, Beatriz Lorena; Ramos Bravo, Michael Alexandre (Ingeniería Solidaria, 2011)
The growing interest towards the implementation of indicators of corporate management to achieve continuous improvement has influenced in the sense that those corporations give a look towards the organizational climate as a determinant factor in the quality and corporate success. This is even more accurate within solidarity economy companies, were different elements of human integration, such as companionship, cooperation, communion, colectivity, charisma (C Factor) play an important role in their productivity. The article presents a review of history and perspectives of the so called “C Factor” as an important element in creating competitive and self-supportive enterprises. Authors reflect on the concept of organizational environment and its importance in the sense of well being experienced by their employees. Finally, the article comments Luis Razetos’s theory (creator of this concept).